1997
DOI: 10.1074/jbc.272.8.4836
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine Mediates the Immediate Negative Inotropic Effects of Tumor Necrosis Factor-α in the Adult Mammalian Cardiac Myocyte

Abstract: To determine whether activation of the neutral sphingomyelinase pathway was responsible for the immediate (<30 min) negative inotropic effects of tumor necrosis factor-␣ (TNF-␣), we examined sphingosine levels in diluent and TNF-␣-stimulated cardiac myocytes. TNF-␣ stimulation of adult feline cardiac myocytes provoked a rapid (<15 min) increase in the hydrolysis of [ 14 C]sphingomyelin in cell-free extracts, as well as an increase in ceramide mass, consistent with cytokine-induced activation of the neutral sph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
196
0
6

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(211 citation statements)
references
References 44 publications
9
196
0
6
Order By: Relevance
“…7,8 Our findings support the predominant role of sphingomyelinceramide signaling pathways in TNF-␣-induced ROS generation and mtDNA decline in cardiac myocytes as well. This is in line with the observation by Oral et al 15 that TNF-␣ may cause a rapid activation of sphingomyelinase, with subsequent sphingomyelin hydrolysis and sphingosine production in cardiac myocytes. Ceramide has been shown to result in an inhibition of electron transport at the level of complex III followed by an increased generation of ROS.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…7,8 Our findings support the predominant role of sphingomyelinceramide signaling pathways in TNF-␣-induced ROS generation and mtDNA decline in cardiac myocytes as well. This is in line with the observation by Oral et al 15 that TNF-␣ may cause a rapid activation of sphingomyelinase, with subsequent sphingomyelin hydrolysis and sphingosine production in cardiac myocytes. Ceramide has been shown to result in an inhibition of electron transport at the level of complex III followed by an increased generation of ROS.…”
Section: Discussionsupporting
confidence: 79%
“…15 Previous studies in various cell types have demonstrated that TNF-␣ exerts a direct effect on mitochondrial function and ROS generation via involvement of sphingomyelin hydrolysis to produce ceramide as a lipid second messenger. 7,8 Our findings support the predominant role of sphingomyelinceramide signaling pathways in TNF-␣-induced ROS generation and mtDNA decline in cardiac myocytes as well.…”
Section: Discussionmentioning
confidence: 99%
“…In its both reduced (GSH) and oxidized (GSSG) forms, glutathione serves as a natural inhibitor of N-SMase [25], which hydrolyzes sphingomyelin into ceramide, controlling the sphingolipid signaling cascade [26][27][28] and mediating TNF-α apoptotic [29] and negative inotropic effects in cardiomyocytes [11,30,31]. Downstream ceramide generation, the ordered cascade of events in N-SMase pathway comprises downregulation of the prosurvival factor Bcl-2, resulting into a decrease of the proapoptotic Bax/ prosurvival Bcl-2 protein ratio that in turn elicits activation of caspase-3 [32].…”
Section: Introductionmentioning
confidence: 99%
“…The negative inotropic effects of TNF-␣ and the role of iNOS-derived nitric oxide in the control of cardiac function have been well characterized both in vitro and in vivo. TNF-␣ depresses myocardial contractility by two mechanisms: Within minutes, it causes acute contractile dysfunction by decreasing calcium transients through a sphingosine signaling intermediate 14 ; within hours, it induces iNOS gene expression, which increases nitric oxide production, leading to sustained contractile dysfunction. 15 iNOS generates nitric oxide at high flux rates, leading to concentrations in the steady state that are 100-to 1000-fold greater than those produced by endothelial or neuronal NOS.…”
Section: See P 1537mentioning
confidence: 99%